Victimology and psychosocial well-being of the elderly in Iwaya community (2019)
Victimology is an infrequently discussed social phenomenon in Nigeria despite its prevalence and grave social implications. Nigerian government does not provide social security for the elderly and the support from the family is fading out, leading to kidnap and abuse of elders. The study examined the relationship between Victimology and psycho-social wellbeing of elders in Iwaya community, Lagos State. Quantitative data were analysed using descriptive and t-test at P value 0.5. The findings revealed that kidnapping and abuse of elders were more experienced outside Lagos State (14.7%) than other places such as within neighbourhood (8%), outside neighbourhood (6.7%), and outside the country' (7.3%). The value of X2 at the .05 level of significance with 1 degree of freedom was 3.841. The computed value of 2.227a was smaller and within the critical value range of 3.841. The null hypothesis that there is no significant relationship between kidnapping of elders and their psychosocial wellbeing was accepted. The value of X2 at 0.5 level of significance with 1-degree freedom was 3.841. Computed value of 4.313a was greater than the critical value of 3.841. The null hypothesis that there is no significant relationship between mistreatment and their psychosocial wellbeing was rejected. Results suggest possible factors such as poor quality of education, high level of poverty, lack of value for hard-work and indiscipline are causes of crime, thus negatively affecting security of lives and properties. Government should address security lapses by providing the security agencies with necessary facilities and environment conducive to combating crime in Nigeria